1997
DOI: 10.1006/viro.1997.8770
|View full text |Cite
|
Sign up to set email alerts
|

The Locus of Epstein–Barr Virus Terminal Repeat Processing Is Bound with Enhanced Affinity by Sp1 and Sp3

Abstract: EBV DNA contains G-rich, repeat regions that are involved in rearrangement and recombination events including terminal repeat (TR) processing and the EBNA-2 deletion in the EBV strain P3HR-1. Cellular proteins, called terminal or tandem repeat binding proteins (TRBPs), recognize sequences at the junctions of these recombination events. In this study, using antibody supershift assays and expression of recombinant proteins, we show that Sp1 and Sp3 are the sequence-specific components of TRBP and that Ku is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Whether this suppression is caused by LANA binding to TR needs to be further investigated in latently infected cells. Interestingly, the TR of EBV also contain Sp1 and Sp3 binding sites, and it has been suggested that these factors do not regulate transcription but might play a role in genome circularization following de novo infection (31,33).…”
mentioning
confidence: 99%
“…Whether this suppression is caused by LANA binding to TR needs to be further investigated in latently infected cells. Interestingly, the TR of EBV also contain Sp1 and Sp3 binding sites, and it has been suggested that these factors do not regulate transcription but might play a role in genome circularization following de novo infection (31,33).…”
mentioning
confidence: 99%
“…[26][27][28][29] Moreover, recently it has been shown that this motif is contained within a 15 bp DNA region that binds a protein complex involved in recombinogenic reorganization of the Epstein-Barr virus genome. 30,31 Here, we show in a functional assay system that this sequence is indeed directly involved in recombination events.…”
Section: Discussionmentioning
confidence: 80%
“…Variation in the copy number of the terminal repeat elements may play a role in viral gene expression and binding of transcription factors such as Sp1 (Figure 2). The Sp1 transcription factor binds immediately adjacent to the cleavage site in the terminal repeat element generating the linear viral form [37], [38].…”
Section: Resultsmentioning
confidence: 99%